Measurement of electrons from heavy-flavour hadron decays in p-Pb collisions at √sNN=5.02TeV - Adam, Jaroslav; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Deisting, Alexander; Fleck, Martin; Glässel, Peter; Karayan, Lilit; Klein, Jochen; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; et al. (Physics letters, 2016)
The production of electrons from heavy-flavour hadron decays was measured as a function of transverse momentum (pT) in minimum-bias p-Pb collisions at sNN=5.02 TeV using the ALICE detector at the LHC. The measurement covers the pT interval 0.5<pT<12 GeV/c and the rapidity range −1.065<ycms<0.135 in the centre-of-mass reference frame. The contribution of electrons from background sources was subtracted using an invariant mass approach. The nuclear modification factor RpPb was calculated by comparing the pT-differential invariant cross section in p-Pb collisions to a pp reference at the same centre-of-mass energy, which was obtained by interpolating measurements at s=2.76 TeV and s=7 TeV. The RpPb is consistent with unity within uncertainties of about 25%, which become larger for pT below 1 GeV/c. The measurement shows that heavy-flavour production is consistent with binary scaling, so that a suppression in the high-pT yield in Pb-Pb collisions has to be attributed to effects induced by the hot medium produced in the final state. The data in p-Pb collisions are described by recent model calculations that include cold nuclear matter effects.
Im Titel ist "NN" nach s tiefgestellt, der ganze Ausdruck "s NN" steht unter dem Wurzelsymbol
Available online 31 December 2015
ALICE collaboration: J. Adam, V. Anguelov, F. Bock, O. Busch, A. Deisting, M.G. Fleck, P. Glässel, L. Karayan, J. Klein, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F.Weiser, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und 956 weitere]
Gesehen am 29.07.2020